Association of atopic dermatitis with inflammatory bowel disease: A systematic review and meta-analysis - Chi-Hui Wang; Yun Fu; Ching-Chi Chi (Wolters Kluwer Medknow Publications, 2020)
Background: Altered microbiota of the gastrointestinal tract have been implicated in both atopic dermatitis (AD) and inflammatory bowel disease (IBD). However, the relationship between AD and IBD has been unclear. Objectives: The objective of this study was to systemically assess the evidence on the association of AD with IBD. Methods: We conducted a systematic review and meta-analysis of observational studies on the association of AD with IBD. We searched MEDLINE, Embase, CENTRAL, Web of Science, and Airiti Library from inception to May 24, 2019, for relevant studies. The outcomes were the odds and risk of Crohn's disease (CD) and ulcerative colitis (UC) in patients with AD. Results: We included five case-control studies and one cohort study. We identified significant associations of AD with prevalent CD (odds ratio [OR]: 1.55, 95% confidence interval [CI]: 1.11-2.15) and UC (OR: 2.49, 95% CI: 1.04-5.98). One Danish cohort study found no increased risk for incident CD (hazard ratio [HR]: 0.69, 95% CI: 0.34-1.30) and UC (HR: 0.94, 95% CI: 0.61-1.43) in patients with AD. Conclusion: The current limited evidence supports an association of AD with prevalent IBD. Digestive symptoms in patients with AD, for example, chronic diarrhea and abdominal pain, shall not be overlooked, and gastroenterology counseling may be needed.